Organizational Culture through Orientations and Metaphors: Some Hints to the Tacit Knowledge - Gerli HÄMMAL; Maaja VADI (Revista de Management Comparat International)
The main goal of our study is to examine the possibilties to lead tacit through a lens of organizational culture assessed by orientations and metaphors. Organizational culture may open important issues because this phenomenon evolves values, assumptions etc which also play significant role in the tacit knowledge transfer. Metaphors intermediate the unconscious levels of organizational culture. Empirical survey among 75 participants was conducted in two industrial enterprises from Saint-Gobain Group in Estonia. The triangulation of different methods was used and a combination of questionnaire and interview was applied for the measurement of organizational culture. Position, education and tenure have important effect on estimations to task orientation. Gender, position and education have important effect on estimations to relationship orientation. The estimations on both orientations are connected to whether the organization is characterized through metaphors to be organic or technocratic. The results are discussed and the consequesnces for tacit knowledge are proposed.